Behavioural and electrophysiological characterisation of experimentally induced osteoarthritis and neuropathy in C57Bl/6 mice - Dickenson Anthony H; Harvey Victoria L (SAGE Publishing, 2009)
Abstract Background Osteoarthritis is a widespread condition affecting the elderly where ~70-90% of over 75 year olds are affected, representing one of the largest cost burdens to healthcare in the western world. The monosodium iodoacetate (MIA) osteoarthritis model has been well described in the rat especially in terms of the pathological progression of the disease and more recently pain behaviour. In this study, we characterise, for the first time, MIA induced osteoarthritis in mice and compare it with nerve-injured mice (partial sciatic nerve injury), using both behavioural and in vivo electrophysiological measurements. These approaches uniquely allow the threshold and suprathreshold measures to many modalities to be quantified and so form a basis for improving and expanding transgenic studies. Results Significant mechanical hypersensitivity was observed in the ipsilateral hindpaw in MIA injected mice at all observed time points following infrapetellar MIA injection (p < 0.05). The mechanical hypersensitivity exhibited a partial biphasic temporal pattern, but thermal hypersensitivity was absent. Electrically-evoked dorsal horn neuronal responses in MIA injected mice were significantly elevated (p < 0.05) with respect to A- and C-fibre firing, input, pinch and noxious von Frey (26 and 60 g). No significant changes in A- or C-fibre thresholds were observed. Nerve-injured mice displayed significant behavioural thermal and mechanical hypersensitivity (p < 0.05) and evoked dorsal horn responses were significantly increased with respect to C-fibre firing, pinch and wind-up (p < 0.05). Conclusion The MIA model of osteoarthritic pain in mice displays behavioural characteristics similar to those observed in rats. Changes in both behavioural measures and neuronal activity from the paw, suggest that central changes are involved in this pain state, although a role for peripheral drives is also likely. Moreover, the behavioural and neuronal measures in these two pain models showed overlapping alterations in terms of certain neuronal measures and mechanical sensitivity despite their very different pathologies and a loss of input in neuropathy, suggesting some commonalities in the central processing of different peripheral pain states. This murine model of osteoarthritis will allow the exploitation of knock out animals to better understand underlying mechanisms and identify novel molecular targets.